(untitled) (Communications in Mathematical Research, 2021)
In this paper, the estimation of parameters based on a progressively type-I interval censored sample from a Pareto distribution is studied. Different methods of estimation are discussed, which include mid-point approximation estimator, the maximum likelihood estimator and moment estimator. The estimation procedures are discussed in details and compared via Monte Carlo simulations in terms of their biases.